Oral Mucositis Prevention and Management by Therapeutic Laser in Head and Neck Cancers - Fekrazad, Reza; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2013)
Introduction: Oral mucositis is considered a severe complication in cancer patients receiving radiotherapy or chemotherapy for head and neck cancer. The aim of this review study was to assess the effect of low level laser therapy for prevention and management of oral mucositis in cancer patients. Methods: The electronic databases searched included Pubmed, ISI Web of Knowledge and Google scholar with keywords as “oral mucositis”, “low level laser therapy” from 2000 to 2013. Results: The results of most studies showed that photobiomodulation (PBM) reduced the severity of mucositis. Also, it can delay the appearance of severe mucositis. Conclusion: Low level laser therapy is a safe approach for management and prevention of oral mucositis.